Thioflavin-T does not report on electrochemical potential and memory of dormant or germinating bacterial spores - Yong-qing Li; Lin He; Makunda Aryal; James Wicander; George Korza; Peter Setlow (mBio, 2023)
ABSTRACT Bacterial spores are metabolically dormant, resistant to microbicides, and vectors of food spoilage and diseases, while germinated spores are easy to kill. Consequently, understanding germination mechanisms may facilitate the development of “germinate-to-eradicate” strategies. Spores germinate in response to many compounds (called germinants). They can also retain the memory of a germinant exposure, such that a second exposure triggers more efficient germination, but how is not clear. A recent high-profile paper [Science (2022) 378:43] suggested that increasing spore electrochemical potential is how memory is “stored” based on measurements of Bacillus subtilis spores’ accumulation of the dye thioflavin-T after germinant exposure. Indeed, we found that wild-type spores of three Bacillus and one Clostridioides species all exhibited this early thioflavin-T accumulation during nutrient pulses. However, our data indicate that inferring spores’ electrochemical potential from thioflavin-T accumulation is problematic. We found that B. subtilis spores lacking their proteinaceous coat exhibited memory but did not accumulate thioflavin-T prior to germinant addition or during nutrient pulses. Furthermore, wild-type Bacillus spores germinating with dodecylamine, which also elicits memory, showed no thioflavin-T accumulation. Finally, we found that thioflavin-T accumulation by a germinating spore is outside the spore core at early stages but inside the spore core as germination proceeds. These findings suggest that thioflavin-T accumulation during the early stages of germination is due to its binding to one or more protein in the spore coat rather than to changes in spores’ electrochemical potential; thus, thioflavin-T is not a potentiometric dye for the study of spore memory of germinant pulses. IMPORTANCE Bacillus and Clostridium spores cause food spoilage and disease because of spores’ dormancy and resistance to microbicides. However, when spores “come back to life” in germination, their resistance properties are lost. Thus, understanding the mechanisms of spore germination could facilitate the development of “germinate to eradicate” strategies. One germination feature is the memory of a pulsed germinant stimulus leading to greater germination following a second pulse. Recent observations of increases in spore binding of the potentiometric dye thioflavin-T early in their germination of spores led to the suggestion that increasing electrochemical potential is how spores “remember” germinant pulses. However, new work finds no increased thioflavin-T binding in the physiological germination of Coatless spores or of intact spores germinating with dodecylamine, even though spore memory is seen in both cases. Thus, using thioflavin-T uptake by germinating spores to assess the involvement of electrochemical potential in memory of germinant exposure, as suggested recently, is questionable.